Functional outcome of proximal humerus fracture treated with proximal humerus interlocking system plating - Harshwardhan, Hemeshwar; Verma, Buddhi Prakash (International Journal of Research in Orthopaedics, 2019)
Background: Proximal humerus fractures account for 4-5% of all fractures. They are the commonest fractures in elderly population, which ranks the third, after hip and distal radius fractures respectively. Displaced fractures treated by pinning, cancellous screws, intra-medullary nails, proximal humeral plates and hemiarthroplasty. The proximal humerus interlocking system (PHILOS) plate is anatomically contoured and the threaded screw heads are locked into the threaded plate holes which allow early rehabilitation. The aim of this study is to evaluate results and complication of PHILOS. Methods: This a prospective study, conducted at JLN Medical College, Ajmer from 1st January 2017 to 31st July 2018. 36 patients of displaced proximal humerus fractures were included and operated at hospital with PHILOS plating. We evaluate Intra-operative events, post-operative radiological evaluations and bony union by NEER’S score and complications. Results: Functional results according to NEER’S score were found that out of 36 patients, 11 patients (30.5%) had excellent outcome, 19 patients (52.7%) have satisfactory outcome, 3 patients (8.33%) had unsatisfactory outcome and 3 patients (8.33%) had poor outcome. Conclusions: Internal fixation of proximal humerus fractures with use of PHILOS yields reliable results when utilized correctly. To achieve gold standard results, early physiotherapy is must which can only be done by stable fixation, ORIF with PHILOS provides more stable construct with anatomical reduction.